Response of the Land‐Atmosphere System Over North‐Central Oklahoma During the 2017 Eclipse. Issue 3 (10th February 2018) - Turner, D. D.; Wulfmeyer, V.; Behrendt, A.; Bonin, T. A.; Choukulkar, A.; Newsom, R. K.; Brewer, W. A.; Cook, D. R.
Abstract: On 21 August 2017, a solar eclipse occurred over the continental United States resulting in a rapid reduction and subsequent increase of solar radiation over a large region of the country. The eclipse's effect on the land‐atmosphere system is documented in unprecedented detail using a unique array of sensors deployed at three sites in north‐central Oklahoma. The observations showed that turbulent fluxes of heat and momentum at the surface responded quickly to the change in solar radiation. The decrease in the sensible heat flux resulted in a decrease in the air temperature below 200 m, and a large decrease in turbulent motions throughout the boundary layer. Furthermore, the turbulent mixing in the boundary layer lagged behind the change in the surface fluxes, and this lag depended on the height above the surface. The turbulent motions increased and the convective boundary layer was reestablished as the sensible heat flux recovered. Plain Language Summary: Turbulent motions in the lower part of the atmosphere are driven strongly by the heating of the surface of the earth by the sun during the daytime. Observations during the 2017 solar eclipse provide a detailed look at how the turbulent nature of the atmosphere changed as the solar energy at the surface responded as the moon moved across the sun during the eclipse. Key Points: The 2017 solar eclipse provides a unique opportunity to evaluate land‐atmosphere interactions Comprehensive surface fluxes and boundary layer profiling observations were made at three sites during the eclipse event The turbulence and stability in the boundary layer evolved dramatically during the event, with time scales that depended on height